2002
DOI: 10.1211/0022357021778600
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant properties of Helichrysum italicum

Abstract: The anti-inflammatory and antioxidant activities of the aerial part of Helichrysum italicum extracts have been established in various in-vivo and in-vitro experimental models. The results obtained on the acute oedemas induced by 12-O-tetradecanoylphorbol 13-acetate (TPA) and ethyl phenylpropiolate in the mouse ear, by serotonin and phospholipase A2 (PLA2) in the mouse paw, on chronic inflammation induced by repeated application of TPA in the mouse ear and on the delayed-type hypersensitivity induced by sheep r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(129 citation statements)
references
References 16 publications
0
118
0
3
Order By: Relevance
“…119 In many cases, increased oxidative stress is a widely associated in the development and progression of diabetes and its complications which are usually accompanied by increased production of free radicals or failure of antioxidant defense. 120 Though the intake of natural antioxidants has been reported to reduce risk of cancer, cardiovascular diseases, diabetes and other diseases associated with aging, there is considerable controversy in this area.…”
Section: Uses Of Antioxidants In Technologymentioning
confidence: 99%
“…119 In many cases, increased oxidative stress is a widely associated in the development and progression of diabetes and its complications which are usually accompanied by increased production of free radicals or failure of antioxidant defense. 120 Though the intake of natural antioxidants has been reported to reduce risk of cancer, cardiovascular diseases, diabetes and other diseases associated with aging, there is considerable controversy in this area.…”
Section: Uses Of Antioxidants In Technologymentioning
confidence: 99%
“…Finally, when chronic inflammation was induced by multiple applications of 2 Pg of TPA, the ear edema was reduced by 65, 44 and 48 % with 200 mg.kg -1 of the methanolic extract, hexane and CH 2 Cl 2 fraction, respectively, whereas the leukocyte infiltration was reduced by all the fractions (40-66 %) and the methanolic extract (58 %). The authors concluded that the anti-inflammatory activity of these extracts might be due to pro-inflammatory enzyme inhibition, free radical scavenging activity or effects similar to the ones induced by corticoids (Sala et al, 2002).…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The outstanding fact is that, use of natural medicine treatments is referred to any age groups and the sex antiviral activities. The ingestion of natural antioxidants has been associated with reduced risks of cancer, cardiovascular disease, diabetes, and other diseases associated with ageing 8,9 .…”
Section: Introductionmentioning
confidence: 99%